The development of matrix measurement guideline of collaborative teamwork environment in construction industry - Nurdiana Azmi, 1984-; Mohamad Ibrahim Mohamad, supervisor; Fakulti Kejuruteraan Awam (2008)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2008